Schulleitungen als Promotoren. Unterstützung digitalisierungsbezogener Schulentwicklungsprozesse durch Schulleitungen und deren Wahrnehmung durch Lehrpersonen. - Gerick, Julia; Kieseler, Janine; Herrmann, Daniel; Eickelmann, Birgit (MedienPädagogik (Occasional Papers))

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.

Schulkulturbezogene Schultypen im Zeitalter der digitalen Transformation. Eine Typologie unter Berücksichtigung von Hintergrundmerkmalen der zur Schulkultur befragten Lehrkräfte - Caruso, Carina; Drossel, Kerstin; Heldt, Melanie (MedienPädagogik)
In view of technological progress, a digitalisation deficit in German schools as well as the experiences in schools as a result of the Corona pandemic, it becomes apparent that the question of a school culture conducive to learning retains its relevance in the age of digital transformation: On the one hand, it is evident that school culture changes in view of the digital transformation. On the other hand, it contributes to the successful implementation of digital media. Previous research findings in connection with the digital transformation focus on particular competencies of teachers (Meyer, Becker, and Bock 2023; Caruso, Heldt, and Drossel 2022; Vogelsang et al. 2023) and their cooperative behaviour (Drossel and Heldt 2022; Schulze, Drossel, and Eickelmann 2022). These questions whether school culture-related school types can be identified or not and how teachers perceive the school culture have been less considered so far. This article is dedicated to this question and explores if the school culture-related school types differ in terms of the background characteristics of the teachers. Based on a Latent Class Analysis, three school culture-related school types become apparent: strong in innovation and cooperation (Type I: 45.74 %), highly innovative and inhibited cooperation (Type II: 17.95 %), inhibited in terms of innovation and cooperation (Type III: 36.31 %). The types do not differ from each other regarding the background characteristics.

Wie entwickeln sich medienbezogene Einstellungen, selbsteingeschätzte Medienkompetenzen und motivationale Orientierungen angehender Lehrkräfte? - Vogelsang, Christoph; Caruso, Carina; Seifert, Andreas; Schwabl, Franziska (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Für die lernförderliche Einbindung digitaler Medien in schulische Lehr-Lern-Situationen sollten angehende Lehrkräfte neben mediendidaktischen sowie medienerzieherischen Kompetenzen auch über medienbezogene motivationale und volitionale Dispositionen verfügen. Insbesondere Einstellungen und selbsteingeschätzte Kompetenzen sind Einflussfaktoren auf die Motivation zur Mediennutzung. Auf Basis einer Sekundäranalyse wird daher in diesem Beitrag die wechselseitige Entwicklung dieser Dispositionen für verschiedene medienbezogene Kompetenzfacetten von N = 269 Lehramtsstudierenden längsschnittlich untersucht, die ein fünfmonatiges Langzeitpraktikum während der Massnahmen zur Eindämmung der CoViD-19-Pandemie im Wintersemester 2020/2021 absolviert haben. Diese Zeit ging mit vermehrten medienbezogenen Lerngelegenheiten einher. Die Ergebnisse zeigen, dass sich die Einstellungen der angehenden Lehrkräfte hinsichtlich der Mediennutzung kaum veränderten, sich selbsteingeschätzte Medienkompetenzen und medienbezogene Motivation hingegen mit kleinem bis mittlerem Effekt positiv entwickelten. Cross-Lagged-Panel-Analysen zeigen zudem, dass sich eine hohe motivationale Orientierung in Bezug auf die Mediennutzung zu Beginn des Langzeitpraktikums positiv auf die Entwicklung selbsteingeschätzter Kompetenzen auswirkte, allerdings nicht in allen in der Analyse betrachteten Kompetenzfacetten.
Keywords: Pharmacology

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.
Keywords: General Medicine

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory